융합인재교육(STEAM)에 대한 유아교사의 관심단계와 활용수준 분석: 관심중심수용모형을 중심으로 - 이수기(Suki Lee) (한국콘텐츠학회 논문지, 21(4), 2021)
The purpose of this study was to investigate the stage of concern and use level of early childhood teachers' STEAM, and to find out whether there is a difference in the stage of concern according to individual teachers' variables. The subjects were 242 teachers in charge of 3-5 years old kindergarten and daycare center in G city. The research tool was the stages of concern questionnaire (SoCQ). The collected data were converted to relative intensity by applying percentile conversion chart in the guidelines, and this was expressed as a concern profile graph, and t-test and ANOVA were performed to find out the difference in concern according to teacher's background variables. The research results are as follows. First, the stage of concern in early childhood teachers' STEAM was identified as a critical non-user profile. Second, the stage of concern in the teacher's STEAM was judged as a person who did not use, or was implemented for less than 2 years, and was a non-user or a novice. In addition, it was found that most of the teachers did not receive formal education for STEAM. third. There were differences in the educational background, career, current execution status of teachers, whether or not to take related courses in pre-service teacher education, and whether to plan for future implementation. And there were no differences in the majors and institution types of teachers. Based on these results, a support plan for changing the stage of concern of teachers about STEAM and improving the level of use was suggested. 본 연구는 유아교사의 STEAM에 대한 관심단계와 활용수준을 조사하고 교사 개인의 변인에 따라 관심단계에 차이가 있는가를 알아보고자 하였다. 연구대상은 G시의 유치원과 어린이집의 3-5세를 담당하는 교사 242명이었다. 연구도구는 관심단계설문지(stages of concern questionnaire: SoCQ)이었다. 수집된 자료는 지침서의 백분위수 환산표를 적용하여 상대적 강도로 변환하고 이를 관심단계 프로파일 그래프로 나타내었고 배경변인에 따른 관심단계 차이를 알아보기 위해 t검증과 ANOVA를 실시하였다. 연구결과는 다음과 같다. 첫째, 유아교사의 융합인재교육에 대한 관심단계는 비판적인 비사용자의 프로파일로 확인되었다. 둘째, 유아교사의 융합인재교육에 대한 활용수준은 대부분의 교사가 전혀 실행하지 않거나 2년 이하로 실행하며 스스로를 전혀 활용안하는 사람이거나 초보적인 활용자로 판단하였고, 대부분의 교사가 융합인재교육에 대한 공식적인 교육을 받지 못한 것으로 나타났다. 셋째. 유아교사의 학력, 경력, 현재 실행여부, 예비교사 교육 시 관련교과 수강여부, 향후 실행계획여부에서는 차이가 있는 것으로 나타났고, 유아교사의 전공, 기관유형에서는 차이가 없는 것으로 나타났다. 이러한 결과를 바탕으로 STEAM에 대한 유아교사의 관심단계를 전환시키고 활용수준을 증진시키기 위한 지원방안을 제언하였다.